Dark State Adiabatic Passage with Branched Networks and High-Spin Systems: Spin Separation and Entanglement - Batey, Caitlin; Jeske, Jan; Greentree, Andrew D. (Frontiers in ICT, 2015)
Adiabatic methods are potentially important for quantum information protocols because of their robustness against many sources of technical and fundamental noise. They are particularly useful for quantum transport, and in some cases elementary quantum gates. Here, we explore the extension of a particular protocol, dark state adiabatic passage, where a spin state is transported across a branched network of initialized spins, comprising one “input” spin, and multiple leaf spins. We find that maximal entanglement is generated in systems of spin-half particles, or where the system is limited to one excitation.